Knowledge and Awareness of Community Pharmacist and Physician about Drug Information Center (DIC) and Its Services - Hadia , Rajesh (Current Progress in Medicine and Medical Research Vol. 6, 2023)
A Drug Information Centre (DIC) is a specialized facility designed to provide accurate, unbiased, and relevant drug information (DI) to both consumers and healthcare professionals. It serves to educate individuals about proper drug usage, drug safety, and addresses critical issues related to drug information, including side effects. The objective of this study was to assess the knowledge of primary care physicians and community pharmacists regarding DIC facilities and raise awareness about its importance. Throughout the study period, a total of 88 participants took part, including 68 (77%) community pharmacists and 20 (23%) primary care physicians. By the end of the study, it was found that 48 (70.2%) pharmacists and 10 (50%) physicians were aware of DI, DIC, Drug Information Query (DIQ), resources available, and the role of pharmacists in DIC. However, the study revealed that overall knowledge about DIC, DI, and DIQ was not extensive among the pharmacists and physicians. This study concludes that there is a lack of awareness regarding the Drug Information Centre (DIC), Drug Information, and its significance in city and address this issue and reduce drug-related problems, it is crucial to conduct various awareness programs that highlight the importance and value of DIC. These efforts will help make DIC more accessible to all individuals and increase understanding and utilization of its services.